Regional performance analysis of the Central-Hungarian Region - Áldorfai, György (Studia Mundi – Economica, 2016)
The survival of a settlement depends highly on the locally invested capital, but to ensure that his capital finds its way to the settlement the local resources must be utilised properly. In Hungary, similarly to other V4 countries, typically the larger cities are the ones that can use their resources in a way that they can attract capital on the long run. This phenomenon is even more common in the close proximities of the capital cities, which makes these areas perform better than the convergence regions. Therefore, many settlements in there become non-eligible for EU funds which could be used for development, and thus, many experts have recommended the separation of Budapest and the rest of the Central-Hungary region, forming two new regions. This study presents an investigation, which illustrates how developed Budapest is compared to the other settlements in the Central-Hungary region, in order to explore the possibility of separation realistically.